The use of saliva and blood progesterone to profile the menstrual cycles of youth professional football players - Ferrer, E.; Rodas, G.; Casals, G.; Trilla, A.; Balagué-Dobon, L.; González, J. R.; Ridley, K.; White, R.; Burden, R. J. (Frontiers in Sports and Active Living, 2024)
Background Understanding individual ovarian hormone cycles and their relationship with health, performance and injuries is highly important to practitioners supporting female athletes. Venous blood sampling is the current gold standard for measuring the ovarian hormones, but the invasive nature of this method presents a major barrier in sport environments. Saliva analysis may offer an alternative method as it is non-invasive, allowing the sample to be collected "in situ", with relative ease, necessary in applied sport environments.